2017
DOI: 10.1155/2017/4956216
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Reveals Related Regulatory Mechanisms of Androgenic Gland inEriocheir sinensis

Abstract: Chinese mitten crab (Eriocheir sinensis) is one of the most commercially important aquaculture species in China. The androgenic gland (AG) of crustaceans plays pivotal roles in the regulation of male differentiation and in maintaining the male sexual characteristics. In order to reveal related mechanisms in AG, we compared transcriptomes of AG between proliferation and secretion phase. A total of 72,000 unigenes and 4,027 differentially expressed genes were obtained. Gene ontology enrichment analysis indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…Insulin-like receptor (IR) functions as the pivotal member of insulin family signaling pathway and directs the male sexual differentiation in mammals [46]. Earlier evidence has shown that IR interacts with the insulin-like androgenic gland hormone (IAG) to regulate sex differentiation and spermatogenesis in crustaceans [13,15,46,47]. In our study, IR has shown higher expression in ovaries than in testes.…”
Section: Discussionsupporting
confidence: 52%
“…Insulin-like receptor (IR) functions as the pivotal member of insulin family signaling pathway and directs the male sexual differentiation in mammals [46]. Earlier evidence has shown that IR interacts with the insulin-like androgenic gland hormone (IAG) to regulate sex differentiation and spermatogenesis in crustaceans [13,15,46,47]. In our study, IR has shown higher expression in ovaries than in testes.…”
Section: Discussionsupporting
confidence: 52%
“…From the couple of stages examined in M. rosenbergii (Sharabi et al, 2016) and S. verreauxi , the same goes for decapods. The only differential expression reported regards an unspecified IR paralog in Eriocheir sinensis: it is up-regulated during the secretion phase of the androgenic gland, compared to the proliferation phase (Fu et al, 2017). This functioning of the gland is related to the exacerbation of sex characters as males ready for mating, but this does not occur in isopods.…”
Section: Targeted Silencing Of Av-ir1 and Av-ir2 By Rnaimentioning
confidence: 97%
“…In addition, with the development of sequencing technology and molecular biology, more sex-related genes have been successfully mined, such as Vasa, Foxl2, Vitellogenin (Vg), Ecdysone Receptor (EcR), Sry, Ftz-f1, etc. [88]- [95], however, there is still a lack of research on the functional mechanisms of genes in sex determination, differentiation and gonadal development.…”
Section: Other Sex Determination and Differentiation-related Genesmentioning
confidence: 99%